2007
DOI: 10.1111/j.1574-6968.2007.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns and role of the CadF protein inCampylobacter jejuniandCampylobacter coli

Abstract: Binding of Campylobacter jejuni and Campylobacter coli to host fibronectin is mediated by the 37 kDa outer membrane protein CadF. Immunoblot analysis of 58 C. jejuni and C. coli isolates of human and animal origin showed that CadF is expressed in every strain. In most C. jejuni isolates, a 37 kDa band (p37) and a less-prominent 32 kDa band (p32) reacted with the antibodies. In C. coli isolates, CadF was consistently larger with sizes of 39 kDa (p39) and 34 kDa (p34), respectively. PCR analysis and sequencing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…2A and B). This protein is a 37-kDa OMP that is essential for C. jejuni colonization of chickens (12,14,17,25,26,51). A reactive band (band 11), corresponding to a protein with a molecular mass of 37 kDa, was observed in the OMP extracts from the C. jejuni S3B and 81-176 strains using each of the nine C. jejuni S3B-SPF sera ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2A and B). This protein is a 37-kDa OMP that is essential for C. jejuni colonization of chickens (12,14,17,25,26,51). A reactive band (band 11), corresponding to a protein with a molecular mass of 37 kDa, was observed in the OMP extracts from the C. jejuni S3B and 81-176 strains using each of the nine C. jejuni S3B-SPF sera ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies identified some adhesion factors of C. jejuni such as CadF (fibronectin-binding outer membrane protein), CapA (the autotransporter), and PEB1 (periplasmic binding protein) (Pei and Blaser, 1993;Konkel et al, 1997). CadF, mediating cell adhesion by attaching to fibronectin, can be considered a key virulence-associated factor because the pathogenicity is significantly reduced in cadF mutants (Ziprin et al, 1999;Krause-Gruszczynska et al, 2007b;Dastia et al, 2010). Furthermore, the invasion ability of Campylobacter is one of the virulence-associated factors because several studies performed on different animal models revealed that mucosal damage at early stages of infection results from invasion of C. jejuni into epithelial cells in the colon (Humphrey et al, 1985;Field et al, 1986;Babakhani et al, 1993).…”
Section: Adhesion and Invasionmentioning
confidence: 98%
“…CadF, CapA, PEB1 Fauchere et al (1986), Konkel et al (1997), Ziprin et al (1999), Krause-Gruszczynska et al (2007b), Dastia et al (2010) Invasion Invasion of C. jejuni results in mucosal damage initially in colon.…”
Section: Introductionmentioning
confidence: 97%
“…Our results showed that the mixed infections usually had a predominant organism with up to 4 logs more bacteria than the other organism. Relevant to quantitation is the fact that most of our targets were single-copy chromosomal genes (aerolysin, cadF, toxR, lysP, and invA) (15,22,25,48). The ipaH target is likely to be less useful, because its copy numbers vary between species (42,47).…”
Section: Discussionmentioning
confidence: 99%